Assessment of the relationship between maxillary rotation and nasal morphology in males - Rajarshi Bhushan; Santosh Kumar; Arun K Chauhan; Stuti Mohan; Manish Shekhar; Aditya Narnoly (Wolters Kluwer Medknow Publications, 2015)
Background: Nasal features are important in treatment planning for orthodontic treatment. Aims and Objectives: The purpose of the study was to assess the relationship between maxillary inclination and nasal morphology in males. Materials and Methods: Forty-five samples were selected for the study between the age group of 18 and 30 years. Selected individuals were subjected to cephalometric radiography. These lateral cephalograms were traced and divided into three groups on the basis of the angle given by Schwarz for rotation of the maxilla. The nasal features of these groups were evaluated and compared using mean, standard deviation, Student's t-test and analysis of variance. Results: The results suggest that there was statistically significant difference in nasal height, nasal bone length (NBL), nasal depth, nasolabial angle (NLA), nasal tip angle and upper lip inclination angle in different maxillary inclination group. Conclusion: The nasal height, NBL, NLA and nasal tip angle had a maximum value in retro inclination group.